Phase Evolution and Thermal Stability of 2 Mg-Cu Alloys Processed by Mechanical Alloying - Bustos-Castillo, O; Ordonez, S; Serafini, D (Elsevier Ltd, 2013)
Phase evolution during mechanical alloying (MA) of elemental Mg and Cu powders and their subsequent heat treatment is studied. Elemental Mg and Cu powders in a 2:1 atomic ratio were mechanically alloyed in a SPEX 8000D mill using a 10:1 ball-to-powder ratio. X-ray diffraction (XRD) shows that the formation of the intermetallic Mg2Cu takes place between 3 and 4 h of milling, although traces of elemental Cu are still present after 10 h of milling. The thermal behavior of different powder mixtures was evaluated by differential scanning calorimetry (DSC). The combination of DSC, heat treatment and XRD has shown a sequence of phase transformations that results in the intermetallic Mg2Cu from an amorphous precursor. This amorphous phase is converted into Mg2Cu by heating at low temperature (407 K). Short MA times and the formation of the amorphous precursor, together with its subsequent transformation into Mg2Cu at low temperatures; represent an advantageous alternative route for its preparation. © 2013 Elsevier B.V. All rights reserved.